2018
DOI: 10.15283/ijsc18031
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Placenta-derived Mesenchymal Stem Cells on T Cells by Regulation of FoxP3 Expression

Abstract: The immunomodulatory effects of mesenchymal stem cells (MSCs) are an important mediator of their therapeutic effects in stem cell therapy and regenerative medicine. The regulation mechanism of MSCs is orchestrated by several factors in both intrinsic and extrinsic events. Recent studies have shown that the dynamic expression of cytokines secreted from MSCs control T cell function and maturation by regulating the expression of FoxP3, which figures prominently in T cell differentiation. However, there is no evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
(34 reference statements)
0
14
0
4
Order By: Relevance
“…Recently, the dynamic expression of cytokines secreted from MSCs was reported to control T cell function and maturation by regulating the expression of FoxP3, prominently in T cell differentiation. Treg cells co-cultured with PMSCs significantly expanded in comparison with others with bone marrow-derived mesenchymal stem cells (BMSCs) [48]. On the other hand, BMSCs should be harvested by an invasive procedure, are uncommon in the adult human bone marrow [49], and their number consequently reduces with the age of the person [50].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the dynamic expression of cytokines secreted from MSCs was reported to control T cell function and maturation by regulating the expression of FoxP3, prominently in T cell differentiation. Treg cells co-cultured with PMSCs significantly expanded in comparison with others with bone marrow-derived mesenchymal stem cells (BMSCs) [48]. On the other hand, BMSCs should be harvested by an invasive procedure, are uncommon in the adult human bone marrow [49], and their number consequently reduces with the age of the person [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the natural course of pregnancy, due to an immuneprivileged environment, the upregulation of T helper 1 cells occur which secrete anti-inflammatory cytokines (IL-4, -5, -9, -10 and -13) and downregulation of T helper 2 cells occur which secrete pro-inflammatory cytokines (IL-1 and -6, INF-γ). P-MSCs inhibit the proliferation of T lymphocytes due to the abundance expression of indolamine 2,3-dioxygenase (IDO) and immunomodulatory cytokines (as shown in Figure 2) (38,39). P-MSCs regulate the maturation of T reg cells than other MSCs.…”
Section: Immunological Cross-talks Of Placental Mscsmentioning
confidence: 99%
“…Absence of signifi cant stimulation of allogeneic lymphocytes by different type of MSCs has been documented [6]. MSC from different sources; Bone Marrow (BM) [7], Placenta (PL-MSC) [8], Umbilical Cord (UC-MSC) [6], Wharton's Jelly (WJ-MSC) [9], Umbilical Cord Lining (CL-MSCs) and Cord Blood (CB-MSCs) [10], Amniotic Membrane (AM-MSC) [6,11], tonsil [12], cornea [13] and Liver [14], Adipose Tissue (AT-MSC) [15], exert their immunomodulatory effect on immune cells. This could confi rm the universal inhibitory effect of MSCs despite their origins or culture environment.…”
Section: Effect Of Origins and Type Of Msc On Magnitude Of Inhibitorymentioning
confidence: 99%
“…Others reported that immunomodulatory functions of MSC could be altered by pro-infl ammatory cytokines such as IL-1b, IL-6 and IL-23. However, suppressive ability and effi cacy of MSC in cell-based therapy was preserved through proinfl ammatory cytokine modulation [60].Effect of nature and treatment of responding immunological cells on MSC response to inhibitory effectExpression of IDO[10,28,65,66], HLA-G[7,63,67,68], LIF[31,69], PGE2[70] , IL-10[11,17,30,32], TGF-B[8,17,32] and other mediators were reported by many researchers despite use of variable culture conditions with different density, ratio, treatment protocol, nature and method of selection of immune cells. MSC act as secretome with universal constitutive secretion of immunomediators as evidenced by several reports worldwide.…”
mentioning
confidence: 99%